The role of COX-2, caspase-1 and IL-17 in pericoronitis-related inflammation due to lower third molar impaction - Adi Prayitno (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2019)
Background: Inflammation of the pericorona due to lower third molar impaction (LTMI) is often diagnosed as pericoronitis. Expression of cyclooxigenase-2 (COX-2) and caspase-1 may be induced by lipopolysacharide (LPS) and cause pyroptosis with minimal inflammation. When LPS activates toll-like receptor (TLR-4), NOD-like receptors containing domain pyrin 3 (NLRP3) inflammasome will activate the release of pro-caspase-1 to caspase-1, followed by the secretion of interleukin (IL)-1β. IL-1β and IL-23 which induces CD4+ Tcells (Th17) to produce IL-17 as a pro-inflammation cytokine. Purpose: This study aimed to identify the respective roles of COX2, caspase-1 and IL-17 in pericoronitis inflammation of the pericorona due to LTMI. Methods: Frozen section samples were produced through LTMI pericorona tissue biopsy using material provided by the Dental and Oral Clinic at Muwardi Hospital, Surakarta. The paraffin block produced was subsequently cut using a clean microtome with the resulting thin slices being placed on an object glass coated with polylysine. A diagnosis of pericoronitis was subsequently made by a pathologist. Immunohistochemical staining for COX-2, caspase-1 and IL-17 was carried out by indirect tyramide signal amplification (TSA) method. Photos were obtained by means of 100X, 200X, 400X and 1000X objective lensed microscopes to qualitatively assess the above mentioned protein expressions. T-Test was conducted in order to establish the difference in expression between the control group and pericoronitis due to LTMI. Results: The presence of a brownish yellow color indicated the expression of COX-2, caspase-1 and IL-17 in pericorona epithelial cells which visible expression categorized as moderate (30-70%). The mean expression of COX-2, caspase-1 and IL-17 was categorized as mild and there was no significant difference between the expression of the three proteins. Conclusion: COX-2, caspase-1 and IL-17 play an important role in the phyroptosis signal of LTMI pericoronitis in cases of low inflammation.